Evaluation of antimicrobial sensitivity pattern of chronic suppurative otitis media in a tertiary care hospital of West Bengal, India - Mondal, Shirsendu; Banerjee, Manasi; Das, Sudip (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Chronic suppurative otitis media is a common infectious disease in our country. The micro-organisms commonly causing the disease and their antibiotic sensitivity pattern is important for treatment. This study was conducted to evaluate the antimicrobial sensitivity pattern of the common microorganisms in patients with chronic suppurative otitis media in our tertiary care hospital. Methods: The study was carried out from July 2013 to December 2013 at the ENT out-patient department of a tertiary care hospital in West Bengal. 100 patients aged 18 to 60 years of either sex, with unilateral or bilateral active chronic suppurative otitis media attending the out- patient clinic were included in the study. Pus samples were collected from the discharging ears and sent for isolating the organisms and susceptibility testing. Results: A total number of 108 ear swabs were collected from the 100 recruited patients of which 15 (13.88%) were sterile and 93 (86.11%) showed presence of organisms. Pseudomonas aeruginosa 41(38%) was the commonest organism isolated, followed by Staphylococcus aureus 25(23.15%). The antimicrobial profile of the microorganisms reveals maximum sensitivity of the isolated organisms to piperacillin and levofloxacin. Conclusions: In our study, Pseudomonas aeruginosa (38%) and Staphylococcus aureus (23.15%) are the major pathogens involved in the etiology of CSOM. The isolates showed maximum sensitivity to piperacillin (41%) and levofloxacin (41%). As piperacillin is available only in parenteral form and is also costly, topical levofloxacin can be recommended in empirical treatment of CSOM.